Long-term follow-up study on deep brain stimulation for post-traumatic dystonia - Chang LIU (Chinese Journal of Contemporary Neurology and Neurosurgery, 2015)
Background Deep brain stimulation (DBS) offers a very promising therapy for medically intractable dystonia. Among different dystonia subtypes, the surgical outcome of primary dystonia is most convincing, while that of post-traumatic dystonia is uncertain. This paper aims to evaluate the effect of DBS on post-traumatic dystonia. Methods Four patients of post-traumatic dystonia treated with DBS on globus pallidus internus (GPi) or subthalamic nucleus (STN) were reviewed and their surgical effect was evaluated. Outcome assessments were based on Burke-Fahn-Marsden Dystonia Rating Scale (BFMDRS) movement and disability scores preoperatively and one month, 6 months, one year and 2 years after surgery. Improvement rate was counted to evaluate the curative effect. Results BFMDRS movement scores were improved by 38.35%, 47.28%, 62.74% and 68.69% respectively, and disability scores were improved by 35.36% , 46.83% , 59.60% and 67.01% respectively. Imaging features of these patients were reviewed. Although the location and size of encephalomalacia differed among these patients, the anatomical features of basal ganglia remained intact. Conclusions With strict selection, DBS may be a promising treatment to ameliorate the symptoms of post-traumatic dystonia. The surgical effect may be sustainable in long term. Anatomical integrity of basal ganglia may be an important factor to predict good outcome.   DOI: 10.3969/j.issn.1672-6731.2015.10.006